The causal relationship between gut microbiota and alopecia areata: a Mendelian randomization analysis - Bi, Dezhao; Tey, Jin Tong; Yao, Dan; Cao, Yutian; Qian, Minyu; Shi, Jianxin; Guo, Shun (Frontiers in Microbiology, 2024)
Background: Increasing evidence suggests a robust correlation between the gut microbiome and alopecia areata. In light of the extensive diversity of gut microbiota, this study aims to utilize state-of-the-art and comprehensive data to explore the causative association between gut microbiota and alopecia areata.Objective: We conducted a Mendelian randomization (MR)-based two-sample study to elucidate the causal relationship between gut microbiota and alopecia areata.Method: Summary information on Ncase =767 and Ncontrol = 394,105 cases of alopecia areata was obtained from the FinnGen study. A total of 473 gut microbial taxa were summarized from the genome-wide association study (GWAS) catalog. The study comprised a forward Mendelian randomization (MR) analysis with the gut microbiome as the exposure factor and alopecia areata as the outcome, as well as a reverse MR analysis with alopecia areata as the exposure factor and the gut microbiome as the outcome. Various analytical methods including inverse variance weighting (IVW), Weighted Median, MR-Egger, Weighted Mode, and Simple Mode were employed. Subsequently, sensitivity analysis was conducted to ensure the robustness of our research findings.Result: This study has established a causal relationship between gut microbiota and alopecia areata. Forward causal analysis revealed causality relationships between 16 gut microbial taxa and alopecia areata, while reverse causal analysis found that there may be a causal relationship between alopecia areata and 16 gut microbial taxa (not statistically significant).Our study findings suggest a causal relationship between gut microbiota and alopecia areata, providing potential guidance for future clinical trials.